A closure study of aerosol optical properties as a function of RH using a κ-AMS-BC-Mie model in Beijing, China. (15th January 2019) - Zou, Jianan; Yang, Shuanghong; Hu, Bo; Liu, Zirui; Gao, Wenkang; Xu, Hanbing; Du, Chaojie; Wei, Jie; Ma, Yongjing; Ji, Dongsheng; Wang, Yuesi
Abstract: The extinction coefficient of aerosol will directly affect the atmospheric visibility, which is influenced by many factors such as aerosol of particle number concentration distribution, chemical composition, relative humidity (RH) and so on. During the period between 25 August and 05 September 2017, the physical and chemical characteristics of aerosol were measured to explore the effect of those factors on the extinction coefficient in Beijing during four environmental conditions (heavy pollution (HP); light pollution (LP); clean (CL); and rainy (RA)). After the new particle formation events during CL2, the ratio of particle number concentrations in the Accumulation mode (Acc) and Aitken mode (Ait) gradually grew from 0.2 (CL2) to 0.7 (LP1), 0.9 (HP) and 0.8 (LP2). The contributions of particle number concentrations to the extinction coefficient were 0.1% (0.1%), 10.5% (1.4%) and 89.4% (98.5%) in the Nucleation mode (Nuc), Ait and Acc, respectively, during CL1 (HP), which revealed that particles with an extinction function were mainly in Acc, especially during polluted days (PDs). The mass percentage of secondary inorganic aerosol (nitrate, sulfate and ammonium) with a greater hydrophilic characteristic was just 12.8% during clean days (CDs), while this rapidly increased to 56.5% during PDs, which was the main reason for the increase in the extinction coefficient. The sensitivity test of the extinction coefficient calculated using different refractive indices indicated that using the refractive index of the average value of a long observation would cause an underestimation of the extinction coefficient. The hygroscopic factors of the aerosol scattering coefficient (f(RH)) were 1.13, 1.59, 1.49 and 1.62 during CL2, LP1, HP and LP2, when RH = 80.0%, respectively. The extinction coefficients calculated by the κ-AMS-BC-Mie model and measured by the sum of the scattering and absorption coefficients were 675.7 and 521.2 Mm −1 under dry conditions during HP, while those values were 855.7 and 661.7 Mm −1 after correcting for RH. When the hygroscopic growth factor (GF) reached 1.1, the range of f(RH) was approximately 1.30–1.38 during all campaigns. Therefore, on PDs with high RH, aerosol with a greater number of hygroscopic components, which are mainly distributed in Acc, will produce a much larger extinction coefficient. Graphical abstract: Measured versus calculated extinction coefficient on (a) dry instruments ambient and (b) fixed ambient RH during seven periods. Image 1 Highlights: Chemical composition measured by HR-ToF-AMS explain the hygroscopicity of aerosol. The RH correction for the calculation of the extinction coefficient is necessary. The sensitivity experiments on the extinction coefficient are evaluated.